(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2025)
Medical tourism is becoming an important economic sector for Central Asian countries, including Uzbekistan. Digitalization plays a key role in improving the efficiency, transparency, and accessibility of medical services. This article examines electronic health records (EHRs), integrated digital platforms, and international experience, as well as prospects for their implementation in the region.